Selection, characterisation and safety of Limosilactobacillus reuteri DSM 32846, an evolved version of DSM 17938 - Ermann Lundberg, L.; Sendelius, M.; Linninge, C.; Pallin, A.; Liu, P.; Pallabi Mishra, P.; Grompone, G.; Roos, S. (Beneficial microbes, 2025)
Predicting probiotic strain properties that translate into beneficial effects in the host is challenging and could be considered the holy grail in developing new probiotics. One approach is to selectively evolve well-studied probiotic strains known to elicit beneficial effects in clinical studies. In this study, Limosilactobacillus reuteri DSM 17938, among the world's most studied probiotic strains, constituted the origin from which the novel strain L. reuteri BG-R46® (DSM 32846) was obtained by exposure to bile, a major stressor of the gastrointestinal tract. The bioactivity of DSM 32846 in preclinical models is documented elsewhere; this work adds crucial strain characteristics, genomic and phenotypic safety profiles, and safety and tolerability in a randomised human study. DSM 32846 was compared to DSM 17938 in terms of tolerance to bile and synthetic gastric juice, with DSM 32846 showing increased bile tolerance and slightly reduced tolerance to gastric pH. Morphological examination by scanning electron microscopy revealed high abundance of extracellular membrane vesicles on the surface of DSM 32846, a previously described bioactive feature of the strain. In addition, the activity of 5-nucleotidase, an adenosine-producing enzyme expressed on the bacterial cell surface and membrane vesicles, was increased in large-scale production batches of DSM 32846 compared to DSM 17938. Phenotypic safety assessment showed that DSM 32846 does not produce any of the evaluated biogenic amines, produces D- and L-lactate with a ratio typical for the species, and lacks haemolytic activity. The minimum inhibitory concentration profile for antibiotics did not raise any safety concerns. A genome safety assessment revealed no antibiotic resistance and virulence genes. DSM 32846 was found safe for human consumption with no differences from the control group in any of the evaluated parameters. In conclusion, L. reuteri DSM 32846 is a safe strain that shows interesting differences to its parent strain DSM 17938.
Keywords: BG-R46®; bile tolerant; DSM32846; Limosilactobacillus reuteri; probiotics